Legal services for the elderly : elder rights handbook - Legal Services for the Elderly, Inc. (Augusta, ME : Legal Services for the Elderly, 2014)
Legal Services for the Elderly ("LSE") is a nonprofit organization that has been helping Maine seniors since 1974. LSE's mission is to provide free, high quality legal services to Maine residents who are aged 60 and over when their basic human needs are at stake. This LSE Elder Rights Handbook was created to help Maine seniors understand some of the legal risks and problems they may encounter as they age.
Planning for the future -- Protecting your money and property -- Homeowner rights -- Rental agreements and tenant rights -- Watch out for scams! -- Managing your debt -- MaineCare and long-term care -- Medicare -- Sources of income & assistance -- Family relationships -- Elder abuse -- Age and disability discrimination -- Immigration -- Dealing with death -- Are you worried about a senior? -- Getting legal help.
Keywords: Older people -- Legal status, laws, etc. -- Maine; Legal assistance to older people -- Maine; Landlord and tenant -- Legal status, laws, etc. -- Maine; Aged -- Long term care -- United States -- Maine; Medicaid -- Maine